The wild vine (Vitis vinifera áp. silvestris) in the riparian forests of Donau and March (Austria): evaluation of genetic divergence, presence of grape viruses, bacterials and soil-borne vectors - Tiefenbrunner, W.=700 1 Regner, F.; Mandl, K.; Leitner, G.; Gangl, H.
(En, Fr, Es)
ilus., 21 ref.
Keywords: VITIS VINIFERA; VARIACION GENETICA; VIRUS; ENFERMEDADES TRANSMITIDAS VECTORES; ORGANISMOS TRANSMITIDOS POR SUELO; BACTERIA; AUSTRIA